Exploring the role of the JEEViKA swasthya mitra helpdesk in improving healthcare access: a qualitative study in tertiary healthcare facilities in Bihar, India - Pragya Kumar; Shamshad Ahmad; Narottam Pradhan; Neha Chaudhary; Haripriya H.; Sarita Kumari; Naveen K. G.; Akanksha Yadav; Rakesh Jha; Md. Ashraf Parwez; Swati Swati; Apolenarius Purty; et al. (BMC Health Services Research)
Abstract Background Rural populations in Bihar, India, face significant healthcare access challenges due to geographical, infrastructural, and financial barriers. The Swasthya Mitra program, initiated by the Bihar Rural Livelihood Promotion Society in collaboration with local and international partners, aims to mitigate these challenges by employing trained community members to navigate patients through the healthcare system. Methods This qualitative study employed in-depth interview and thematic analysis to evaluate the Swasthya Mitra program in the Bhagalpur and Jamui districts in Bihar, India. The participants included Swasthya Mitras, healthcare professionals, and beneficiaries. This study focused on understanding the role of Swasthya Mitras in facilitating healthcare services. Findings The program improved healthcare access for rural populations, with beneficiaries reporting reduced navigational confusion, decreased out-of-pocket expenditures, and enhanced patient care. Swasthya Mitras bridged the gap between the community and healthcare facilities. The program also empowered women, both Swasthya Mitras and beneficiaries, by improving their access to healthcare and increasing their involvement in health-related decision-making. Interpretation The Swasthya Mitra program may offer a viable model for improving healthcare access in rural settings, demonstrating the importance of community involvement in healthcare delivery. The findings suggested that such programs can be instrumental in overcoming barriers to healthcare access and reducing financial burdens on vulnerable populations. Funding The study was supported by the Bihar Rural Livelihood Promotion Society supported by the World Bank and Project Concern Internation India.